Pulsatilla saxatilis (Ranunculaceae), a new species from north-east China - Zhang, Ting-Ting; Zhang, Shu-Mei; Xu, Liang; Kang, Ting-Guo (Phytotaxa, 2022)
Pulsatilla saxatilis (Ranunculaceae), a new species from Fengcheng in Liaoning province, north-east China, is described and illustrated. Gross-morphologically this species is closely similar to P. chinensis in having 3-foliolate leaves, solitary, erect flowers, and persistent, prolonged styles in fruiting period, but differs by having light blue, whitish-blue or white (vs. violet) sepals and persistent styles 2–2.5 cm (vs. 3.5–6.5 cm) long. Pollen morphology also lends strong support for the description of the new species, with P. saxatilis having pantoporate pollen grains while its putative closest ally, P. chinensis, having tricolpate ones.